The factors that influence nurse anxiety in handling COVID-19 patients - Made Suandika; nasihhudin - -; Debi Ari Setiawan; Tophan Heri Wibowo; Tri Sumarni; Dwi Astuti; Refa Teja Muti; Mariah Ulfah (Riset Informasi Kesehatan, 2023)
Background : Health workers are a group with a very high risk of exposure during the treatment process of covid-19 patients. Many nursing staff have mental health disorders, as they not only bear the overload, high risk of infection, and fatigue. Many factors are the cause of anxiety experienced by health workers during the Covid-19 pandemic such as age, gender, education, employment, and marital status. The purpose of the study was to find out the factors that influence nurse anxiety in handling covid-19. Method : Design survey research with correlational study type using cross sectional time approach. The samples in this study were all nurses who treated covid-19 patients at who were 53 nurses with total sampling techniques. Results : Research instrument using Zung Self Rating Anxiety Scale questionnaire with data analysis using spearman-rank. The results showed nurse anxiety in handling Covid-19 mostly in the mild category (60.4%). Conclusion : There is a relationship between age(p value: 0,0001) and working period(p value: 0,002) factors with nurse anxiety in handling Covid-19 (p value < 0.05). There is no relationship of gender factors, education, and marital status with nurse anxiety in handling Covid-19 (p value > 0.05).